Analysis of the effect of bundled airport privatization on an airline network. (August 2022) - Tani, Ryuichi; Takashima, Ibuki; Kato, Teppei; Tamura, Toru; Uchida, Kenetsu
Abstract: Depopulated regions face declines in traffic demand for airline service. The airline network in Hokkaido, Japan, plays an important role in the regional economy, healthcare, and sightseeing. Toward maintaining this airline network, the "bundled privatization" of airports has been discussed. Under such a system, several airports are privatized as a package for management by a single company. This study proposes a model for analyzing the behaviors of airport operators, airline companies, and passengers when bundled privatization is introduced to an airline network. Under bundled privatization, an airport management company can determine the landing fees of all airports such as to maximize the profits of all its airports, while an airline company can determine its service frequencies and aircraft sizes such as to maximize its profit. As a result of these two profit-maximization behaviors, an equilibrium state is obtained. The proposed model is applied to the airline network in Hokkaido, and the results of numerical calculations are discussed. Highlights: We discussed the impact of the bundled airport privatization on the airline network. We modeled the behaviors of users, airport managers, and airline companies. The airport managers decide the landing fees of their airports under the bundled privatization. The airline companies decide the service frequencies and aircraft sizes. The numerical calculation is performed in the airline network of Hokkaido as an example.